THE EFFECT OF WORKLOAD ON EMPLOYEE PERFORMANCE INOFFICE OF PUBLIC SERVICE MALK (MPP) OF BARRU REGENCY - Kurniawan, Agung Widhi; Ruma, Zainal; S, Aan Arivaldi (Jurnal Manajemen, 2025)
Abstract: This study aims to determine the effect of workload on employee performance atPublic Service Mall (MPP) Office of Barru Regency.The population in this study wasThe population that will be taken by the researcher in this study is the Superiors and Employees of the Public Service Mall (MPP) Office of Barru Regency which consists of 16 service agency units.The sampling of this study used purposive sampling so that three agencies were selected as research samples, namely the Licensing Unit, Disdukcapil (Population and Civil Registration Service), and BPKSDM (Human Resource Development and Personnel Agency). The data used are primary data and secondary data obtained using a questionnaire distribution technique. The results of the study after the data was processed with SPSS.24 showed that there was a positive influence between the Workload variable (X1) on Employee Performance (Y) which can be shown through a simple linear regression equation, namely Y = 31.366 + 0.510 X + e and has a significant effect on the value??????? 4.829 where the overall level used by the author is 0.05 and the degree of freedom with the formula, (a = 5% / 2). df = n - k (72-2) shows a value of 1.994 meaning that the workload variable has a significant effect on employee performance variables. The determination value (R Square) is 0.429. This means that 42.9% of Employee Performance is influenced by the Workload variable in this study, while the remaining 57.1% is influenced by other variables outside the independent variables used in this study. Based on this description, it can be concluded that Workload has a positive and significant effect because a high workload can challenge employees to complete the work.Keywords: Workload, Employee Performance